Source of polynuclear aromatic hydrocarbons found in sediment in a region of expanding sugarcane cultivation of São Paulo State, Brazil - Pantano, Glaucia [UNESP]; Ferrizzi, Vitor C. [UNESP]; Bisinoti, Márcia C. [UNESP]; Moreira, Altair B. [UNESP] (My University, 2016)
Purpose: Polycyclic aromatic hydrocarbons (PAHs) are unintentional products that are classified as persistent toxic substances. The goal of the present study was to generate data on the presence of 15 priority PAHs that are found in surface sediment and core sediment in the region of the Turvo/Grande watershed, São Paulo State, Brazil, which is an area of expanding sugarcane cultivation, and to correlate these data with the sources of these PAHs and the guiding values for sediment quality analysis. Materials and methods: Surface sediments and sediment cores were sampled during the rainy and dry seasons in February and July 2010. The extraction of PAHs from sediments was performed using a Soxhlet extractor, and then the extract was cleaned according to the methods of the US EPA 3630C (US EPA 1996) using a silica gel column. Quantification was performed using high performance liquid chromatography with fluorescence detection. Results and discussion: The concentrations of all 15 PAHs decreased as the depth of the sediment core increased. Overall, the concentrations decreased along the sediment core; however, the RTURARG (region predominantly used for planting sugarcane and livestock) during the rainy season and the CAPRP sampling site (located at part of the Preto River dam) during the dry season showed increased concentrations in the first few sediment fractions, and then the concentrations decreased. Higher concentrations were observed in urban locations, and the concentration of naphthalene was higher than the probable effect level (PEL) determined by the Canadian environmental agency. The obtained diagnostic ratios indicate that the sediment from areas with an abundance of sugarcane was a pyrolytic source of PAHs, which indicates a contribution from burning straw to the PAH concentrations in those areas. Conclusions: For all sampling sites and all PAHs, we found a decreasing trend in PAH concentrations with increasing sediment core depth, and the locations, such as CAPRP, that experienced a higher level of human activity had the highest total concentrations of PAHs. These locations were the only areas in which the PAH naphthalene was found in higher concentrations than the PEL. The diagnostic ratios reveal that regions with sugarcane plantations had predominantly pyrolytic sources of PAHs, indicating the contribution of PAHs from sugarcane straw burning.
Keywords: Diagnostic ratios; PEL; Polynuclear aromatic hydrocarbons; Sediment; TEL